“The future ain’t what it used to be”: World growth and global governance - Díaz-Bonilla, Eugenio (2018)
There is currently a key debate about the future of global governance and what the G20 can do in that regard (Snower, 2018). Here I focus on just one aspect of that broader discussion: what should we expect of global economic growth in the next decade or so, considering that the challenges for national and global governance would be different depending on the type and pace of world economic growth.